A Stalled Revolution? Misoprostol and the Pharmaceuticalization of Reproductive Health in Francophone Africa - Suh, Siri (Frontiers in Sociology, 2021)
Misoprostol entered the global market under the name Cytotec in the mid-1980s for the treatment of gastric ulcers. Decades of research have since demonstrated the safety and effectiveness of off-label use of misoprostol as a uterotonic in pregnant women to prevent and treat post-partum hemorrhage, treat incomplete abortion, or terminate first-trimester pregnancy. Global health experts emphasize misoprostol’s potential to revolutionize access to reproductive health care in developing countries. Misoprostol does not require refrigeration, can be self-administered or with the aid of a non-physician, and is relatively inexpensive. It holds particular promise for improving reproductive health in sub-Saharan Africa, where most global maternal mortality related to post-partum hemorrhage and unsafe abortion occurs. Although misoprostol has been widely recognized as an essential obstetric medication, its application remains highly contested precisely because it disrupts medical and legal authority over pregnancy, delivery, and abortion. I draw on fieldwork in Francophone Africa to explore how global health organizations have negotiated misoprostol’s abortifacient qualities in their reproductive health work. I focus on this region not only because it has some of the world’s highest rates of maternal mortality, but also fertility, thereby situating misoprostol in a longer history of family planning programs in a region designated as a zone of overpopulation since the 1980s. Findings suggest that stakeholders adopt strategies that directly address safe abortion on the one hand, and integrate misoprostol into existing clinical protocols and pharmaceutical supply systems for legal obstetric indications on the other. Although misoprostol has generated important partnerships among regional stakeholders invested in reducing fertility and maternal mortality, the stigma of abortion stalls its integration into routine obstetric care and availability to the public. I demonstrate the promises and pitfalls of pharmaceuticalizing reproductive health: despite the availability of misoprostol in some health facilities and pharmacies, low-income and rural women continue to lack access not only to the drug, but to quality reproductive health care more generally.